Organizational Commitment As A Mediating Variable Of The Influence Of Organizational Climate On Employee Performance - Julindrastuti, Dijah; Karyadi, Iman (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Organization is one of the places needed by an employee to develop their skills and also as a place to meet needs. In running its operations, the existence of an employee is one of the factors that greatly determines the success of an organization. An organization that is able to provide a good work climate and has a good commitment will be able to bring comfort in working so that it will have a good influence on employee performance. Good employee performance will have a positive impact on the success of the organization. Creating a sense of comfort in working can be done in various ways, including by paying attention to employee needs, appreciating employees, establishing good cooperation with employees. In addition to a sense of comfort or also called a good organizational climate, there is a good commitment in running the company. Good organizational commitment will also make employees work well because they have confidence and trust in the company. Researchers are interested in conducting research entitled "Organizational commitment as a mediating variable in the influence of organizational climate on employee performance". The population used in this study were non-educational employees at a college "X". The sample taken in the study was 50 non-educational employees who had a minimum work period of 20 years. This sampling technique used purposive sampling. To answer the hypothesis in the study, the SEM analysis technique was carried out using AMOS 16.0 where this technique was used to determine the role of organizational commitment as a mediating variable. The results of this study are that organizational climate has a significant effect on organizational commitment with a result of 0.027, organizational climate does not affect employee performance with a result of 0.183, organizational commitment affects employee performance with a result of 0.008 and organizational commitment is able to mediate organizational climate and employee performance by 2.478> 1.96.